2000
DOI: 10.1038/sj.bmt.1702207
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of BCR-ABL transcripts in CML patients in cytogenetic remission after interferon-α-based therapy

Abstract: Summary:We measured using a competitive quantitative polymerase chain reaction-capillary electrophoresis (PCR-CE)-based assay, the levels of bcr-abl transcripts in 44 patients with chronic myeloid leukemia (CML) after interferon-␣ (IFN-␣) therapy, who achieved a major (10 patients, MCR group) or complete (34 patients, CCR group) cytogenetic response. All 34 CCR patients had molecular evidence of residual disease detected in bone marrow samples at the time of best karyotypic response. The median number of bcr-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…31,32 With IFN-␣, although several patients achieve a complete and stable CgR, a molecular negativity is rarely seen, but the greater the reduction of BCR/ABL transcripts the better the long-term outcome. 22,25,33,34 AlloHSCT induces a CHR and a CCgR in almost all cases. Longitudinal molecular studies after alloHSCT have shown that a small amount of transcript can be detected within 1 year from transplantation, but that once the transcript becomes undetectable, the disease is almost always cured.…”
Section: Discussionmentioning
confidence: 96%
“…31,32 With IFN-␣, although several patients achieve a complete and stable CgR, a molecular negativity is rarely seen, but the greater the reduction of BCR/ABL transcripts the better the long-term outcome. 22,25,33,34 AlloHSCT induces a CHR and a CCgR in almost all cases. Longitudinal molecular studies after alloHSCT have shown that a small amount of transcript can be detected within 1 year from transplantation, but that once the transcript becomes undetectable, the disease is almost always cured.…”
Section: Discussionmentioning
confidence: 96%
“…In many cases the BCR/ABL transcript was always detectable, in some cases it was occasionally undetectable, and in a few cases it was always undetectable, as has been reported by several investigators over the last 10 years. [24][25][26] These registry data are not presented in more detail because they have been produced over a long period of time, in many different laboratories, and with different techniques. These data cannot contribute more to the debate on the concept of the cure of CML.…”
Section: Complete Cytogenetic Responders To Ifn-␣ In CML 3079mentioning
confidence: 99%
“…It is widely recognized that the specificity of a conventional cytogenetic evaluation is relatively low and it has been reported that the leukemia-specific BCR/ABL transcript can be found in almost all the cases of CCgR. [24][25][26] However, those having a CCgR have less residual disease than other responders [24][25][26] and there is little doubt that CCgRs are a fascinating élite of patients who have the highest sensitivity to IFN-␣ and are the most likely candidates for prolonged survival and possibly cure. 5,17,23,27 For these reasons, better knowledge of more CCgRs is required and this is possible only through an international cooperative effort.…”
Section: Introductionmentioning
confidence: 99%
“…A major step forward was the introduction in recent years of replaceable polymer solutions as separation or sieving media, including linear polyacrylamide (6 -11), cellulose derivatives (8,12,13), and poly(ethylene oxide) (14,15). These advances in matrix preparation have promoted the application of CE in DNA analysis, such as mutation detection (16 -20), forensic genotyping (21,22), DNA sequencing (5,10,15), and measurement of gene expression (23)(24)(25).…”
Section: Academic Pressmentioning
confidence: 99%